Second generation hybrid polar compounds are potent inducers of transformed cell differentiation. - Richon, V M (1996)
Hybrid polar compounds, of which hexamethylenebisacetamide (HMBA) is the prototype, are potent inducers of differentiation of murine erythroleukemia (MEL) cells and a wide variety of other transformed cells. HMBA has been shown to induce differentiation of neoplastic cells in patients, but is not an adequate therapeutic agent because of dose-limiting toxicity. We report on a group of three potent second generation hybrid polar compounds, diethyl bis-(pentamethylene-N,N-dimethylcarboxamide) malonate (EMBA), suberoylanilide hydroxamic acid (SAHA), and m-carboxycinnamic acid bis-hydroxamide (CBHA) with optimal concentrations for inducing MEL cells of 0.4 mM, 2 microM, and 4 microM, respectively, compared to 5 mM for HMBA. All three agents induce accumulation of underphosphorylated pRB; increased levels of p2l protein, a prolongation of the initial G1 phase of the cell cycle; and accumulation of hemoglobin. However, based upon their effective concentrations, the cross-resistance or sensitivity of an HMBA-resistant MEL cell variant, and differences in c-myb expression during induction, these differentiation-inducing hybrid polar compounds can be grouped into two subsets, HMBA/EMBA and SAHA/CBHA. This classification may prove of value in selecting and planning prospective preclinical and clinical studies toward the treatment of cancer by differentiation therapy.